ISOLASI DAN PENGAMATAN MORFOLOGI KOLONI BAKTERI KITINOLITIK - Fitri, Lenni; Yasmin, Yekki (Universitas Syiah Kuala, 2011)
The research is aimed to isolate and observe the morphology of chitinolitic bakteria. The research was conducted since November 2010 until Apryl 2011 at Microbiology Laboratory ofMathematics and Sciences Faculty, University of Syiah Kuala. The method used is experimental method. Locations of water sample taken are at sea, river, and embankment which taken in some areas around Banda Aceh and Aceh Besar. The results showed that there are 18 pure cultuated chitinolitic bacteria isolates. And the results of morphologycal bakteria colony showed that all isolates were circle shape colony. It was found that the flat shape of colony is 14 isolates and 4 serrated. The sizes of colony were found from 1,0 mm until 3,5 mm. The white isolate are 13 and 5 yellowish. The most of isolates are negative gram which bacil and coccus cell shape.